Diabetes Prevention and Screening in the Metropolitan Lisbon Area - Costa, Luciana (2017)
Objectives and Area of intervention: Main aim - To address the hypothesis that low socioeconomic populations are at an increased risk to develop diabetes; Main objectives - To promote health in vulnerable communities in the Lisbon Metropolitan Area, especially to detect undiagnosed diabetes and high-risk individuals.